The role of episodic simulation in the display of prosocial behaviors in competitive environments of intergroup contexts - Alean Molinares, Daniela José (2023)
This study examined the moderation effect of episodic simulation on the relationship between competitive environments and prosocial behaviors in intergroup contexts. In a sample of 120 university students from Santa Marta, Colombia, it was observed that the presence of a competitive environment decreases the prosocial behaviorscompared to non-competitive environments. Episodic simulation does not alter the probability of prosocial behaviors manifestation in competitive environments. These results contrast with previous research and suggest the influence of various methodological and contextual factors. Implications for the design of future research addressing episodic simulation and intergroup dynamics are discussed, highlighting the need to consider more ecological and realistic conditions in research paradigms